2020
DOI: 10.3390/plants9020266
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacterial Microbiome Diversity in Early Developmental Stage Plant Tissues of Wheat Varieties

Abstract: Endophytic bacteria are an important part of different functions in plants that lead to plants’ production characteristics as well as their stress response mechanisms. Endophytic bacterial diversity was analyzed in this study to describe 16S rRNA variability and changes in the leaves of drought-tolerant and drought-susceptible wheat when growth under in vitro conditions. A metagenomic analysis was applied and a pilot exploratory study was performed to prove this type of analysis as applicable to tracking endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…Furthermore, there is some information in the literature that the phenomena of, for example, the accumulation of starch and the loss of water during the seed maturation process seem to favor endophytes that are tolerant to high osmotic pressure [ 4 , 32 ]. Consequently, the endospore formation can also be an important feature for seed colonizers, as it protects them from changes occurring inside the seed [ 32 , 33 ]. The heatmaps presented in Figure 2 and Figure 4 included: (1) bacteria that were present in at least 10 reads and (2) bacteria that were present in at least three samples (or two samples for the in vitro plants).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is some information in the literature that the phenomena of, for example, the accumulation of starch and the loss of water during the seed maturation process seem to favor endophytes that are tolerant to high osmotic pressure [ 4 , 32 ]. Consequently, the endospore formation can also be an important feature for seed colonizers, as it protects them from changes occurring inside the seed [ 32 , 33 ]. The heatmaps presented in Figure 2 and Figure 4 included: (1) bacteria that were present in at least 10 reads and (2) bacteria that were present in at least three samples (or two samples for the in vitro plants).…”
Section: Discussionmentioning
confidence: 99%
“…The endophytic bacterial communities are known to shift with respect to age of plant and environmental factors [6,38]. Most of the earlier studies have focused on analyzing the endophytic bacteria at specific plant growth stages in wheat [1,8,39,40]. The present work emphasizes the study on distribution of nitrogen-fixing endophytic bacteria in wheat crop during different developmental phases.…”
Section: Discussionmentioning
confidence: 99%
“…PCoA also showed that endophytic communities from C. pilosula parts with drought treatment were distinguishable from those in untreated parts. The endophytic bacteria in wheat under drought stress were definitely different from those in control samples [ 44 ]. Previous studies showed that the increase in endophytic diversity and the variation in composition were beneficial to the formation of complexes and stable networks, which might enhance the endophyte, endophyte–endophyte, and endophyte–plant interaction to implement the potential functions of the microorganism [ 41 ].…”
Section: Discussionmentioning
confidence: 99%